The relationship between care dependency and pain in nursing home residents. (September 2020) - Hoedl, Manuela; Bauer, Silvia
Highlights: Pain prevalence differs between independent and dependent resident. Pain level seems be correlated with the degree of care dependency. Pharmacological pain management differs between independent and dependent resident. Abstract: Context: Pain is a common health problem experienced by up to 57 % of nursing home residents which has many negative side effects, including a reduced quality of life. Several studies have been carried out on the prevalence of pain and pain management. However, these study findings remain controversial. Objectives: Therefore, the aim of this study was to compare care dependent and care independent nursing home residents with regard to their (1) pain prevalence and levels and (2) their pain management. Methods: This cross-sectional study is conducted annually in Austrian nursing homes. We measured pain prevalence and levels by asking questions about the pain experienced and pain level measured in the seven days prior to the interview, as well as the pain experienced at the time of this interview. Results: The study sample comprised 81.1 % of the 1528 residents of Austrian nursing homes. Overall, pain prevalence was higher in care dependent residents than in care independent residents. Care dependent residents experienced more often mild/moderate pain than care independent residents. Both, prevalence and levels of pain were not statistically significant different between the levels of care dependency. Care dependent residents who suffered from pain received a statistically significantly higher number of non-pharmacological interventions as compared to care independent residents who suffered from pain. Conclusions: We identified a higher prevalence of pain among care dependent residents. Furthermore, the found differences in pain relief seem to be correlated with different degrees of care dependency, an aspect that requires further investigation.